2020
DOI: 10.13102/sociobiology.v67i3.5148
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sampling techniques and influence of environmental variables on ants in forest fragments in an oil extraction area in the Amazon

Abstract: Around the world, urban landscapes are environments modified by man, generally related to low diversity. The efficiency of a biodiversity inventory is linked to the choice of the sampling technique since the taxonomic and ecological responses of the taxons vary between methods. Here we investigate differences in the ant’s composition sampled using three different techniques in two fragments of the urban forest in the Brazilian Amazon. We also assessed whether the different techniques maintained the same ecolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 67 publications
(72 reference statements)
2
5
0
Order By: Relevance
“…The difference between estimated and observed number of species (57%‐170%) and sampling completeness were moderate (36.07%‐63.36%). However, these patterns of species accumulated curve and sampling completeness are recurrent fact in ant assemblages diversity studies (Leal et al, 2012; Souza & Araújo, 2020). Although there is overlap among the species accumulation curves, this mainly happen among sampling areas with similar forest cover (e.g., 96.55 – 100%), which markedly accumulated more ant species than those with lower forest cover (e.g., sampling areas 10 and 11, respectively, with 13.31 and 24.58%) (see Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…The difference between estimated and observed number of species (57%‐170%) and sampling completeness were moderate (36.07%‐63.36%). However, these patterns of species accumulated curve and sampling completeness are recurrent fact in ant assemblages diversity studies (Leal et al, 2012; Souza & Araújo, 2020). Although there is overlap among the species accumulation curves, this mainly happen among sampling areas with similar forest cover (e.g., 96.55 – 100%), which markedly accumulated more ant species than those with lower forest cover (e.g., sampling areas 10 and 11, respectively, with 13.31 and 24.58%) (see Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…We also collected environmental variables related to soil (clay content, pH, organic matter, sodium, phosphorus, and potassium concentration) due to their influence on invertebrates in previous studies in the Amazon region (Aguiar et al 2006;Tarli et al 2014;Dambros et al 2017;Souza and Araújo 2020;Torres et al 2020). In each fragment, 12 soil samples were collected along the aforementioned transects (same points as for Berlese and Winkler samples) using an auger.…”
Section: Methodsmentioning
confidence: 99%
“…Soil characteristics and vegetation structure are the most frequently tested predictors in distribution models of edaphic organisms (Costa et al 2015;Dambros et al 2020). Environmental factors such as soil texture and chemistry generate microhabitat variability that can affect the spatial distribution pattern of invertebrates at local scales (Mezger and Pfeiffer 2011), as has been determined in the Amazon for oribatid mites (Moraes et al 2011), cockroaches (Tarli et al 2014), termites (Dambros et al 2017), and ants (Souza and Araújo 2020;Torres et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The collection of ants from the plants was performed using the beating technique with capture in entomological umbrella. Thus, 3 branches of similar size and shape of each plant were beaten 10 times and the dislodged insects were collected in the entomological umbrella (Kuchenbecker & Fagundes, 2018;Souza & Araújo, 2020). This was done in the morning from 8 to 11 h. All insects sampled from each plant were properly conditioned in individual plastic containers and transported to the Laboratory of Conservation Biology of the State University of Montes Claros, where they were screened.…”
Section: Methodsmentioning
confidence: 99%
“…Vegetation traits, such as plant size, canopy cover and abundance and richness of plant species have been used as environmental heterogeneity measures to explain ant diversity (Fonseca & Benson, 2003;Queiroz et al, 2017;Silva et al, 2017). In general, more heterogeneous habitats have greater diversity of ants because they have more microhabitats for nesting and greater availability of food resources (Davidson et al, 2003;Fonseca & Benson, 2003;Souza & Araújo, 2020). Positive relationship between ant species diversity and habitat heterogeneity seems to be a common phenomenon, but some studies also have shown negative or absence of a relationship between habitat heterogeneity and ant species diversity (Lassau & Hochuli, 2004;Ribbons, 2014).…”
Section: Introductionmentioning
confidence: 99%